2018
DOI: 10.1007/s10157-018-1612-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterising skeletal muscle haemoglobin saturation during exercise using near-infrared spectroscopy in chronic kidney disease

Abstract: Using NIRS, we have determined for the first time in CKD, that favourable SMO% kinetics (slower deoxygenation rate, quicker recovery) are associated with greater exercise capacity. These dysfunctional kinetics may indicate reduced mitochondria capacity to perform oxidative phosphorylation-a process essential for carrying out even simple activities of daily living. Accordingly, NIRS may provide a simple, low cost, and non-invasive means to evaluate muscle O kinetics in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Our results indicate, as in the study of Wilkinson et al (2019), that as exercise intensity increases, a decrease in SmO 2 occurs, to a point at which an inflection appears. This is shown in the tablet graphics with a colour change (Humon, 2020).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results indicate, as in the study of Wilkinson et al (2019), that as exercise intensity increases, a decrease in SmO 2 occurs, to a point at which an inflection appears. This is shown in the tablet graphics with a colour change (Humon, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…Measuring SmO 2 can be a good way of controlling the intensity of exercise and adapting it to the needs of the person (Wilkinson et al, 2019). To accomplish this, it would be interesting to have studies that confirm the usefulness of SmO 2 , relating it to the data obtained with traditional techniques of performance assessment, assuming the peculiar responses of these subjects.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 3, only one small study (24 cases and 6 controls) up to date has evaluated muscle oxygenation via NIRS in nondialysis CKD patients. In this study, Wilkinson et al [88] described NIRS-derived skeletal muscle O 2 saturation changes during and following exercise and found that CKD patients have dysfunctional kinetics that may indicate reduced mitochondria capacity to perform oxidative phosphorylation. Moreover, there are few studies examining muscle oxygenation via NIRS in ESKD individuals.…”
Section: Assessment Of Endothelial Dysfunction In Ckd: Functional Metmentioning
confidence: 87%
“…Patients with mitochondrial dysfunction are unable to adequately use O2 for oxidative phosphorylation; instead, lactic acid accumulates early in exercise, which leads to exaggerated circulatory and ventilatory responses [ 33 ]. Research by our group showed greater than normal deoxygenation of skeletal muscle hemoglobin in CKD patients during an incremental exercise test, which we hypothesized to indicate reduced mitochondrial and oxidative phosphorylation capacity [ 34 ]. We have also recently shown that at the cellular level, exercise training has no effect on mitochondrial mass or the mRNA expression of key proteins involved in mitochondrial biogenesis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%